Transformative civic education based on social issues: reconstructing students’ civic disposition and participation skills through the project citizen model - Sumaryanto, Riski; Herwin; Damayanti, Ika (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
This study aims to analyze the effect of the social-problem-based Project Citizen model on the civic disposition and participation skills of elementary school students. The study employed a quantitative approach using a quasi-experimental design (nonequivalent control group design). The study subjects consisted of two classes: an experimental class that received instruction using the social-problem-based Project Citizen model and a control class that used an inquiry-based learning model. Data collection was conducted through a questionnaire to measure civic disposition and an observation sheet to assess participation skills. The data were analyzed using an independent samples t-test and MANOVA. The results indicate that the social issue-based Project Citizen model has a significant effect on civic disposition with a significance value of 0.006 (